Suitability of Acrocarpus fraxinifolius as a Pulping Raw Material - Ashwath, M. N.; Sathish, B. N.; Akshayakumari, A.; Rashmitha, H. R.; Alex, Leosh D.; Devagiri, G. M (International Journal of Economic Plants, 2023)
The present study emphasized on wood trait indices of Acrocarpus fraxinifolius for understanding the suitability of the species for paper and pulp industries. The study was conducted at the College of Forestry, Ponnampet, Karnataka in 2020. The wood core samples were collected from the trees falling under 130 to 150 cm girth class, standing in coffee-based agroforestry systems of Kodagu, Karnataka, India. A total of 12 wood core samples were collected using the Presseler’s increment borer at breast height level. For wood fibre analysis the core portion was divided and three, i.e., near to the pith portion, middle and periphery, and made as a composite sample. Core samples were macerated using Jeffreys solution technique at Forest Product and Utilization Laboratory, College of Forestry, UAHS, Shivamogga. Fifty measurements on fibre parameters (Fibre length, Fibre width, Fibre wall thickness, and Fibre Lumen width) were recorded for each sample under a stereomicroscope with an inbuilt Image Analyzer. The mean fibre properties recorded, were used for calculating wood anatomical indices such as the Runkel ratio, Slenderness ratio, Flexibility coefficient, and Rigidity coefficient using standard formulas. The mean Runkel ratio, Slenderness ratio, Flexibility coefficient, and Rigidity coefficient were 0.580, 60.132, 63.290, and 0.184 respectively. The anatomical screening suggests that the species can be used as raw material for paper production, based on the indices. Further research is required to explore the mechanical and chemical properties of commercial exploitation for pulping.